The Influence of Overconfidence, Herding Behavior, and Risk Tolerance on Stock Investment Decisions: The Empirical Study of Millennial Investors in Semarang City - Dea Adielyani; Wisnu Mawardi (Jurnal Maksipreneur, 2020)
The objective of this research is to examine the effect of overconfidence, herding behavior, and risk tolerance to the stock investment decisions. The hypotheses are overconfidence, herding behavior, and risk tolerance have a positive and significant effect on investment decisions. This study is quantitative research, with the population is millennial investors in Semarang City, Central Java, Indonesia. The research used 98 respondents was taken using purposive sampling. The data collected through questionnaires with Google form. The method of data analyze used multiple linier regressions with the application of Statistical Package for the Social Sciences (SPSS) version 22. The results showed that the overconfidence, herding behavior, and risk tolerance provided a positive and significant effect on stock investment decisions of millennial investors in Semarang City.